EVALUASI PERFORMANCE LEAD APRON - Atin Nikmawati; Siti Masrochah (Perhimpunan Radiografer Indonesia (PARI), 2018)
Background : Lead apron is the most important part of set protection radiation personal in Radiology Instalation. Lead apron in Radiology instalation Roemani Muhammadiyah Semarang hospital had been test on 2014. But there is no test after that. The testing standard is 12-18 months at once or when it is needed, so this time the test should be done. This aim of the research are to know physical condition, lead apron profile, treatment and maintenance of lead apron, the result of the test and worthyness of lead apron. Methods: The Type of this research is quantitative research with survey approach. Research use observation, testing, measuring and documentation. Observation done immediately toward the lead apron condition. Lead apron test also done by ilumination of all lead apron surface use x-ray machine. The data from this research then checked with measuring crease, torn, crack, hole and inequality colour use software in computed radiography and desribed later. Result: The result of the research indicate that the Lead Apron number 1 and 2 have bad condition and crack more than 15mm2 in vital organ and more than 670 mm2 in non vital organ. Lead Apron number 3,4,5 have good condition, but has creases and some Lead Apron have inequality colour, Lead Apron number 6 has crease that cause a torn, but still in normal criteria. Lead Apron number 7 has a good condition with not crease. Conclution: Two out of seven Lead Apron are declared not appropriate, dan five out of seven Lead Apron are declared appropriate, further can created Amount of Appropriate Lead Apron percentage which is five lead apron (71%) in appropriate condition and two lead apron (29%) in not appropriate condition.